Introduction: Refreshing Keats's Lamia Volume. Issue 2 (4th March 2022) - Bates, Brian
ABSTRACT: This collection of nine essays celebrates the bicentennial of Keats's last lifetime volume— Lamia, Isabella, The Eve of St. Agnes, and Other Poems (1 July 1820 [Figure 1]). We aim to challenge prevailing stories about the 1820 volume and identify new ways to consider its thirteen poems. Our methodologies include book history, cultural studies, and formalist reading practices; authorship, genre, and reception theories; economic, political, transnational, gendered, racial, religious, and scientific contexts. Our hope is to stimulate ever new readings and appreciations of the poems in this astonishing volume.